Case Report: A case of radioactive iodine-refractory thyroid cancer accompanying cervical lymph node metastasis treated with US-guided RFA combined with 125I seed implantation - Zhai, Yuanpeng; Shao, Yu; Li, Qian (Frontiers in Oncology, 2022)
Background: Local control of metastases is critical to improving the life quality of patients with radioactive iodine-refractory (RAIR) thyroid cancer accompanying regional lymph node metastasis. Case report: The reported patient suffered from RAIR thyroid cancer accompanying poorly controlled cervical lymph node metastasis. The patient's lesions were controlled through 125I seed implantation combined with ultrasound-guided radio-frequency ablation (US-guided RFA). Such a combination therapy has not been reported to date. Conclusion: This study found US-guided RFA combined with 125I seed implantation to be safe and effective for the control of cervical local metastases in patients with RAIR thyroid cancer.